P1142DICHLOROACETATE AND L-CARNITINE REDUCED TGF-BETA-INDUCED MESOTHELIAL-TO-MESENCHYMAL TRANSITION. (6th June 2020) - Masola, Valentina; Arduini, Arduino; Bonomini, Mario; Gambaro, Giovanni; Zaza, Gianluigi
Abstract: Background and Aims: Mesothelial to Mesenchymal Transition (MMT) plays a main role in the induction of peritoneal fibrosis in long term peritoneal dialysis. Mesothelial cells exposed to high glucose produce great amount of TGF-beta that plays a pivotal role in MMT. Recent findings suggest that TGF-beta controls mesothelial fibrosis via the activation of hyperglycolysis, thus we suppose that coupling glycolysis with Krebs cycle may improve mesothelial cells tolerance to TGF-beta. Method: To test this hypothesis, we assessed the effects of Dichloroacetate (DCA), a pyruvate dehydrogenase kinase inhibitor, and L-carnitine (which sustains the production of Acetyl-CoA in multiple ways) on mesothelial cells treated with TGF-beta. Recent findings, in fact, highlight the potential anti-fibrotic effects of DCA and L-carnitine (through energy metabolic balancing) in different organs. Particularly, human peritoneal mesothelial cells (HMrSV5) were cultured in Dulbecco's Modified Eagle Medium (DMEM; Gibco) containing 10% fetal bovine serum. Then, cells, cultured to confluence, were pre-treated for one hour with or without 10mM DCA, 1 or 5 mM L-Carnitine and then with 10ng/ml TGF-beta for 4 hours. Gene expression of alpha-SMA and vimentin (markers of MMT) and IL1-beta and IL-6 (inflammatory markers) was evaluated by real-time PCR. Results: Our results revealed that TGF-beta significantly increased the gene expression level of alpha-SMA (2.04±0.3, p<0.05 versus control) and vimentin (1.61±0.23, p<0.05 versus control) as well as the expression level of the pro-inflammatory cytokines IL1-beta (3.44±0.87, p<0.05 versus control) and IL-6 (2.56±0.51, p<0.05 versus control). Pre-treatment with DCA and L-carnitine (at 1 or 5 mM) significantly reduced these effects. In detail, pre-treatment with DCA reduced alpha-SMA expression (0.97±0.24, p<0.05), vimentin (1.03±0.1, p<0.05), IL1-beta (1.47±0.16, p<0.05) and IL-6 (0.88±0.28, p<0.05) respect to TGF-beta treated cells. Pre-treatment with 1 and 5 mM L-carnitine reduced respectively alpha-SMA expression at 0.96±0.09 (p<0.05) and 0.98±0.06 (p<0.05), vimentin 1.01±0.12 (p<0.05) and 1.02±0.1 (p<0.34), IL1-beta 1.02±0.15 (p<0.05) and 1.68±0.33 (p<0.05), and IL-6 0.72±0.04 (p<0.05) and 0.85±0.01 (p<0.05) respect to TGF-beta treated cells. Conclusion: These preliminary results suggest, for the first time, that the use of both Dichloroacetate and L-carnitine, coupling glycolysis with Krebs cycle and oxidative phosphorylation, could restore physiological energy metabolism in mesothelial cells and control fibrosis.